The impact of HIV/AIDS on low income earners and their propensity to save : a case study of HIV-positive persons in Chiawelo, Soweto township, Gauteng - Joseph, Kakinda (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.